An empirical study on the communication effect of Xiaogang short video: taking Xiaogang Village Red Brigade short video as an example - Chai, Yi (International Journal of Global Economics and Management, 2024)
The story of Xiaogang Village began in 1978. The protagonists of the story - 18 villagers of Xiaogang Village, Fengyang, Anhui Province, demonstrated the pioneering "big contract spirit" to the world through groundbreaking reform practices. The 44-year road of rural reform and development has written a new chapter for Xiaogang Village. The "Xiaogang Spirit" of "dare to create, dare to take responsibility, and dare to struggle" has become an important core of China’s rural revitalization strategy. The report of the 20th National Congress of the Communist Party of China and the government work report of the two sessions both pointed out that we must comprehensively deepen reform and opening up and promote rural revitalization. This article aims to study the publicity effect of the Red Brigade short video in Xiaogang Village under the integration of the Red Brigade, explore and summarize the optimization strategy of short video communication in Xiaogang Village, shoulder the mission of the times with practical actions, and help rural revitalization.